A retrospective study of extrapulmonary tuberculosis in the Khuzestan province of southwest Iran between 2002 and 2023 - Mohammad Hashemzadeh; Aram Asareh Zadegan Dezfuli; Nazanin Ahmad Khosravi; Fatemeh Jahangiri Mehr (BMC Infectious Diseases)
Abstract Background Worldwide, tuberculosis (TB) is among the most common causes of death. To our knowledge, there has been no study showing the prevalence of EPTB in Khuzestan province. Therefore, the objective of this research was to investigate the prevalence of EPTB in patients with or without pulmonary TB in different cities of Khuzestan province from 2002 to 2023. Additionally, the correlation between patient’s gender, and age groups with the disease was also investigated. Methods In this retrospective study, the existing records in Tuberculosis Regional Reference Laboratory of Khuzestan province related to patients were used. The research was carried out by investigating the archive information in 19 years (from 1st January 2002 to December 30, 2023). All confirmed cases of EPTB and simultaneous EPTB and PTB, based on laboratory results and medical examination were included in the study. Patients with incomplete information and military TB were excluded from the study. Information collected from patients includes age, gender, involved organ, place of residence, and year of disease. Results A total of 12,900 EPTB-related medical records were extracted from Tuberculosis Regional Reference Laboratories in southwest Iran, Ahvaz. After excluding records, 12,836 clinically diagnosed or laboratory-confirmed tuberculosis patients were included in this study, including 5991 patients with simultaneous PTB and EPTB, and 6845 patients with EPTB only. The mean age of male EPTB patients was 37.5 years (SD ± 14.6), while the mean age of male patients with simultaneous PTB and EPTB was 45.8 years (SD ± 15.3). The mean age of female patients with EPTB only, and with simultaneous PTB and EPTB was 31.2 years (SD ± 12.6), and 31.5 years respectively. Discussion tuberculosis is a systemic disease with different clinical manifestations. This study described different epidemiologic patterns of concurrent EPTB. The proportion of different types of EPTB was simultaneously determined for a group of hospitalized patients and shown to be different with gender and age. This study will likely increase clinicians’ awareness of the disease and help them better address diagnostic challenges and improve treatment outcomes for patients with EPTB.